The effect of nano-calcium carbonate on β-glucosidase immobilized by alginate and chitosan - Mariam Iqbal; Yuefeng Deng; Qiaoyue Chen; Chengli Yang; Yihui Zhu; Ziqian Chen; Jianjun Wang; Kaishun Hu; Guanya He; Dali Li (Green Synthesis and Catalysis, 2022)
Nanotechnology has become the most promising domain to boost the efficiency of enzymes. Enzymes are vital as a green catalyst in many industries, food, pharmaceutical and biomedical, etc. The immobilization process of the enzyme increases its catalytic properties. In this research, a novel method is presented to describe the effect of nano-calcium carbonate on the characteristics of immobilized β-glucosidase, which was extracted from the Agrocybe aegirit. The nano-CaCO3 was produced using the eco-friendly natural deep eutectic solvent. The pure nano -CaCO3 was observed as vaterite, with a size of about 300 nm. The nano-calcium carbonate was coated by a natural polymer sodium alginate compound and then adsorbed chitosan. Further, this obtained composite is cross-linked by the bioactive genipin to immobilize the β-glucosidase. The enzyme/protein loading ratio to the supports was 1:4, respectively. The recovery efficiency of immobilized β-glucosidase was 89.3%, and immobilization yield was 96.452%. Chitosan-coated nano-CaCO3 was used as a carrier for immobilization of β-glucosidase to improve its stability and reusability. In addition to stability and reusability, pH tolerance, temperature tolerance, and enzyme kinetics are the significant parameters that illustrate the proficiency of an immobilized enzyme. The measured optimal enzymatic reaction conditions for the immobilized β-glucosidase were 50 °C and pH 6. Furthermore, it has shown noticeable improvements in thermo-stability and pH tolerance. Temperature tolerance was observed 50% to the initial activity of the immobilized enzyme even after the 3 h of incubation at 50 °C, while pH tolerance was noticed more than 50% and 40% at pH 7 and 8, respectively. The Km and Vmax values of free and immobilized β-glucosidase to 4-nitrophenyl β-D-glucopyranoside were 1.549 μmol/L/min, 0.346 mmol/L and 0.532 μmol/L/min, 0.080 mmol/L, respectively. The immobilized β-glucosidase retains its storability 80% even after 30 days of storage at 4 °C and maintains 93.1% of its residual activity by reusing up to 10 cycles.